2020
DOI: 10.1159/000506048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sociodemographic Characteristics on the Quality of Care in the Surgical Management of Endometrial Cancer: An Analysis of a National Database in the United States

Abstract: Introduction: Quality of care is an emerging concern, notably in oncology. The aim of the present study was to identify the sociodemographic factors influencing the quality of care in the USA concerning the surgical management of endometrial cancer (EC) through the Surveillance Epidemiology and End Results (SEER) database using already published Belgian quality indicators (QI). Methods: Using the SEER database 1988–2013, we identified 151,752 patients treated for EC. Six QI were extracted from a Belgian study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This finding was consistent with other studies that have demonstrated an increase in cancer research papers from China [17,18]. In addition, we noticed that not only Chinese scholars, but also scholars from France [19,20], South Korea [21,22], Japan [23], Italy [24], and Switzerland [25], have used the SEER database to conduct clinical cancer research.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with other studies that have demonstrated an increase in cancer research papers from China [17,18]. In addition, we noticed that not only Chinese scholars, but also scholars from France [19,20], South Korea [21,22], Japan [23], Italy [24], and Switzerland [25], have used the SEER database to conduct clinical cancer research.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, the mortality caused by endometrial cancer had been found to be the highest among women of low socioeconomic status, 25 possibly because of reduced evidence‐based care. 26 …”
Section: Introductionmentioning
confidence: 99%
“…2 The mortality rate is higher in low socio-economic countries due to a lack of evidence-based care. 3,4 The management essentially includes surgical staging followed by adjuvant treatment in the form of radiotherapy and/or chemotherapy. Adjuvant radiotherapy is delivered through external beam radiation therapy (EBRT) and intravaginal brachytherapy (IVBT).…”
Section: Introductionmentioning
confidence: 99%